Hubungan Platelet–Lymphocyte Ratio dengan Luas Lesi Paru pada Pasien Tuberkulosis Paru di RSUD Abdul Moloek tahun 2023-2024 - Muhammad Ricky Ramadhian; Sindika Amertavia; Ayu Tiara Fitri; Syazili Mustofa (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2026)
Background:. Pulmonary tuberculosis remains a major health problem and requires a simple marker to assess disease severity. The platelet-lymphocyte ratio (PLR) has been widely studied as an indicator of inflammation, but its relationship with lung lesion extent remains inconsistent. This study aimed to assess the relationship between PLR and lung lesion extent in pulmonary tuberculosis patients at Abdul Moloek Regional Hospital. Methods: This study used a cross-sectional design with a total sampling technique. A total of 52 patients who met the inclusion and exclusion criteria were analyzed. PLR data were obtained from complete blood counts, and lesion extent was assessed using chest radiography. Spearman correlation analysis was used to test the relationship between the two variables. Results: The distribution of lesion extent showed the largest proportion in the extent category. PLR values ??varied significantly between subjects. The Spearman test showed a correlation coefficient of 0.084 with a p-value of 0.553, indicating no significant relationship between PLR and lung lesion extent. Conclusion: This study concluded that PLR is not associated with lung lesion extent in pulmonary tuberculosis patients. PLR cannot be used as a radiological marker to assess the severity of lung damage, so additional parameters or a multimodal approach are needed in clinical evaluation